Geringqualifizierte Arbeitnehmer:innen im Ausbaugewerbe im Land Bremen: Qualifizierungsbedarfe und -strukturen - Andreas Friemer; Peter Bleses (Institut Arbeit und Wirtschaft (IAW), Universität Bremen und Arbeitnehmerkammer Bremen, 2024)
Die 3D-Transformation - Digitalisierung, demografischer Wandel und Dekar- bonisierung - stellt neue Anforderungen an Arbeitskräfte in diversen Bran- chen und Berufen. Besonders betroffen von den Veränderungen durch die Dekarbonisierung ist das Ausbaugewerbe, das eine zentrale Rolle bei der Umsetzung der Energiewende im Gebäudebereich spielt. Gleichzeitig leidet diese Teilbranche des Baugewerbes jedoch stark unter Fachkräftemangel. Ein ungenutztes Potenzial zur Rekrutierung von Fachkräften liegt hier in der Gruppe der Helferinnen und Helfer im Ausbaugewerbe, die bislang allerdings kaum in Qualifizierungsmaßnahmen eingebunden werden. Die Studie zeigt, dass das regionale Weiterbildungsangebot im Land Bremen die geringqualifizierten Arbeitnehmerinnen und Arbeitnehmer noch nicht erfolgreich adressiert, weil die bestehenden Angebote rein fachlich ausge- richtet sind und auch nur zum Teil berufsbegleitend wahrgenommen wer- den können. Um die Energiewende erfolgreich umzusetzen, bedarf es neuer, niedrigschwelliger Qualifizierungswege und Weiterbildungsketten, die auf die Bedürfnisse dieser Zielgruppe zugeschnitten sind. Betriebe sollten das Potenzial von Geringqualifizierten im Ausbaugewerbe stärker in den Blick nehmen und sie bei der schrittweisen Qualifizierung hin zum Berufsabschluss proaktiv unterstützen. – – The so-called 3D transformation - digitalisation, demographic change, decarbonisation - is creating new demands on employees in many professions and sectors. In particular, the component of "decarbonisation" and "energy transition" has an impact on the finishing trade. The employees are particularly important for the energy transition in the building sector. Today the finishing trade in particular is affected by the shortage of skilled workers. For companies it is increasingly difficult to recruit new specialists, keep long-term staff and acquire sufficient junior staff via the dual training system. However, in the finishing trades, there is still untapped potential for skilled workers in the group of helpers, who carry out unskilled activities as non-skilled workers and unskilled activities as support for the skilled workers. This group of employees has not yet been taken into account when it comes to tackling the energy transition. However, in order to exploit this potential, planning and qualification is needed as well as matching qualification offers are required. For helpers in the finishing trade, there are only a few low-threshold further training opportunities in the state of Bremen. The regional range identified in the study mainly consists of completion-oriented measures that rely almost exclusively on the quantum leap in the qualification of helpers towards skilled workers - mostly via post-qualifications (NQE) or partial qualifications (TQ). However, as practice shows, these offers are often very challenging for the target group. Many trained and unskilled employees have discontinuous vocational biographies. Hence, the qualification offers do not reach the target group to the desired extent. In order to adequately take into account the "stumbling blocks" for low-skilled workers, the prevailing subject-centered view should be significantly broadened for all actors involved: companies, training institutions and facilities for the promotion of qualifications. After all, professional qualification is a prerequisite and requires assistance. Participants are confronted with special challenges through long durations of completion-oriented measures, but also through new learning methods in terms of their motivation. Their cognitive abilities as well as their willingness and ability to persevere need to be addressed. Training offers must be broadened both professionally and interdisciplinary in order to be able to cover the needs of interested parties as precisely as possible. And there is a need for successive training chains. Ideally, it is based on low-threshold initial qualifications as well as supplementary basic education offers. This is followed by holistic qualification offers leading to vocational qualification. Such training chains are fundamental. Employees must be exempted from work by the companies for this purpose - i.e. receive a participation guarantee. Financially, they must be able to rely on a support guarantee for the required period. And training institutions must ensure that all successive sub-qualifications are actually offered on site - i.e. guaranteeing the availability of trainings.
Keywords: 330